Prioritized Expression of BTN2 of Saccharomyces cerevisiae under Pronounced Translation Repression Induced by Severe Ethanol Stress - Yamauchi, Yukina; Izawa, Shingo (Frontiers in Microbiology, 2016)
Severe ethanol stress (>9% ethanol, v/v) as well as glucose deprivation rapidly induces a pronounced repression of overall protein synthesis in budding yeast Saccharomyces cerevisiae. Therefore, transcriptional activation in yeast cells under severe ethanol stress does not always indicate the production of expected protein levels. Messenger RNAs of genes containing heat shock elements can be intensively translated under glucose deprivation, suggesting that some mRNAs are preferentially translated even under severe ethanol stress. In the present study, we tried to identify the mRNA that can be preferentially translated under severe ethanol stress. BTN2 encodes a v-SNARE binding protein, and its null mutant shows hypersensitivity to ethanol. We found that BTN2 mRNA was efficiently translated under severe ethanol stress but not under mild ethanol stress. Moreover, the increased Btn2 protein levels caused by severe ethanol stress were smoothly decreased with the elimination of ethanol stress. These findings suggested that severe ethanol stress extensively induced BTN2 expression. Further, the BTN2 promoter induced protein synthesis of non-native genes such as CUR1, GIC2, and YUR1 in the presence of high ethanol concentrations, indicating that this promoter overcame severe ethanol stress-induced translation repression. Thus, our findings provide an important clue about yeast response to severe ethanol stress and suggest that the BTN2 promoter can be used to improve the efficiency of ethanol production and stress tolerance of yeast cells by modifying gene expression in the presence of high ethanol concentration.